The Impact of Tax Planning, Profitability, and Leverage on the Value of Listed Logistics Companies - Sitorus, Alvin David P; Tarmidi, Deden (WIM Solusi Prima, 2024)
The COVID-19 pandemic significantly impacted businesses worldwide including in Indonesia. The COVID-19 pandemic's unprecedented impact on businesses has prompted a surge in research examining its effects on firm value. This study aims to analyse the value of the company after before and after the COVID-19 period and analyse the impact of tax planning, profitability and leverage. The logistics sector has an important role in business activities, including the delivery of health products during the pandemic. There are 36 transport and logistics companies sampled using purposive sampling method in this study with the research years 2018 to 2022. Using multiple linear regression analysis, the results of this study prove the effect of tax planning on firm value, while profitability and leverage cannot be proven. These results offer valuable insights for investors in the transportation and logistics sector. By incorporating tax planning information alongside traditional financial metrics, investors can make more informed investment decisions. Keywords: Tax Planning, Profitability, Leverage, Firm Value